Wupperthal : strategy for action : a case-study in co-operative rural development - Kaplan, Alan Louis (Department of Environmental and Geographical Science, 2023)
This study documents an attempt to employ a direct-action strategy within the rural community of Wupperthal in order to combat rural stagnation and disintegration, to reduce poverty, and to promote development. The direct-action strategy employed was that of helping people to form themselves into co-operative enterprises, thus utilizing the concepts of participation and control in order to raise levels of responsibility, initiative and critical awareness. The study documents the difficulties experienced and analyses the causes of, and reasons for, the successes achieved, and the failures encountered. It also discusses some of the dangers of First World intervention in a Third World community. It ends by suggesting ways in which the co-operative direct-action strategy may be extended and improved in order to make it more efficacious in the long term.